Tingkat Pengetahuan berhubungan dengan Tingkat Kecemasan Masyarakat terhadap Pandemi Covid-19 Tahun 2021: The Level of Knowledge is Related to the Level of Public Anxiety About the 2021 Covid-19 Pandemic - Dian Susiana; Lannasari (MPI Press, 2023)
Introduction: Knowledge greatly impacts one's mental status and of course enriches one's life. Knowledge has distinctive characteristics such as ontology (about what), epistemology (how) and for what (axiology). Knowledge greatly influences a person's behavior. It is expected that everyone who has good knowledge will also have good behavior. Anxiety is a negative emotion that can be felt by humans, the emergence of tense feelings and thoughts, usually accompanied by symptoms of fast heartbeat, sweating, and shortness of breath. Purpose: To find out the relationship between the level of knowledge and the level of public anxiety in Kampung Grogol Depok RT 01 RW 06 about the Covid-19 pandemic in 2021. Method: The method used is a cross-sectional analytic approach with a nonprobability sampling technique to be more precise, namely purposive sampling. The sample obtained was 154 respondents. Retrieval of data using a questionnaire instrument, the data was tested using Spearman correlation analysis. Results: Based on the Spearman Rank correlation test, the p-value was obtained: 0.001 <0.05. Conclusion: From the results of the research conducted, there is a relationship between the level of knowledge and the level of community anxiety in Kampung Grogol Depok, RT 01 RW 06, regarding the Covid-19 pandemic with a sufficient level of closeness, namely 0.270. then H0 is rejected and Ha is accepted.